Keypunching / Third Edition - Hanson Peggy (Prentice Hall, 1977)
This book places special emphasis on the detailed examination of specific skills needed to become a proficient operator, such as job analysis and program preparation, procedures and techniques for simplifying the job, and step-by-step instruction for accomplishing a job from beginning to end. Basics, Introduction, Preliminary Instructions, Car Punching (SF(Bquipment, The Program Card, Card Verifying Equipment, Multiple-Level Punching, Index.s